2019
DOI: 10.1021/acsnano.9b04367
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Dependent Photoinduced Electron Transfer in 0D–2D Lead Sulfide/Cadmium Sulfide–Layered Molybdenum Disulfide Hybrids

Abstract: We demonstrate layer-dependent electron transfer between core/shell PbS/CdS quantum dots (QDs) and layered MoS2 via energy bandgap engineering of both donor (QD) and acceptor (MoS2) components. We do this by changing (i) the size of the QD or (ii) the number of layers of MoS2 and each approach alters the bandgap and/or the donor-acceptor separation distance, thus providing a mean of tuning the charge transfer rate. We find the charge transfer rate to be maximal for QDs of smallest size and for QDs combined wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(93 citation statements)
references
References 42 publications
4
89
0
Order By: Relevance
“…Recently, Chen et al demonstrated interfacial electron transfer in core‐only PbS–MoS 2 and core/shell PbS/CdS–MoS 2 hybrids ( Figure ). [ 102 ] As shown in Figure 8a–c, the size of the QDs and the number of MoS 2 layers are changed to alter the bandgap and furthermore tune the charge‐transfer rate of the heterojunction. Layer‐dependent electron transfer between core/shell PbS/CdS QDs and layered MoS 2 via energy bandgap engineering indicated that five‐layer MoS 2 provides an effective charge‐transfer method for 2D MoS 2 with QD hybrid devices.…”
Section: Band Alignment Strategies and Mechanism In Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Chen et al demonstrated interfacial electron transfer in core‐only PbS–MoS 2 and core/shell PbS/CdS–MoS 2 hybrids ( Figure ). [ 102 ] As shown in Figure 8a–c, the size of the QDs and the number of MoS 2 layers are changed to alter the bandgap and furthermore tune the charge‐transfer rate of the heterojunction. Layer‐dependent electron transfer between core/shell PbS/CdS QDs and layered MoS 2 via energy bandgap engineering indicated that five‐layer MoS 2 provides an effective charge‐transfer method for 2D MoS 2 with QD hybrid devices.…”
Section: Band Alignment Strategies and Mechanism In Photodetectorsmentioning
confidence: 99%
“…Layer‐dependent electron transfer between core/shell PbS/CdS QDs and layered MoS 2 via energy bandgap engineering indicated that five‐layer MoS 2 provides an effective charge‐transfer method for 2D MoS 2 with QD hybrid devices. [ 102 ] Hu et al combined light‐sensitive PbS QDs with 2D WSe 2 to develop hybrid PbS/WSe 2 phototransistors with a responsivity of up to 2 × 10 5 A W −1 and a specific detectivity over 10 13 Jones in both ON and OFF state. [ 103 ] For this structure, PbS QDs can efficiently absorb the incident illumination whereas the WSe 2 layer serves as a transport path for photogenerated carriers.…”
Section: Band Alignment Strategies and Mechanism In Photodetectorsmentioning
confidence: 99%
“…Indeed, Chen at al. 100 used this method to demonstrate the existence of interfacial CT in both core/shell PbS/CdS QD− MoS 2 and core-only PbS QD−MoS 2 hybrids.…”
Section: Acs Energy Lettersmentioning
confidence: 99%
“…Chen et al 100 developed core/shell PbS/CdS QD−MoS 2 hybrids for potential sensing in the NIR range. The PbS/CdS core/sell QDs and layered MoS 2 form a type II heterojunction (Figure 7a), facilitating electron transfer from the photoexcited QDs to layered MoS 2 .…”
Section: Acs Energy Lettersmentioning
confidence: 99%
“…Heterostructures of 0D/2D materials combine the advantages of the two materials and have attracted considerable research interest in recent years. [ 15–18 ] The responsivity of hybrid PbS QDs/graphene phototransistors reach 10 7 A W −1 , which is attributed to the photogating effect through capacitive coupling. However, most of such detectors exhibit large dark current, small on‐off ratio (<2), and slow photoresponse due to the semimetallic nature of graphene.…”
Section: Introductionmentioning
confidence: 99%